Wood waste quantification from the furniture industry in Ubá (Brazil) and its reuse prospects in civil construction - Gomes, Roziani Maria; Gonçalves Tibiriçá, Antônio Cleber; Franco de Carvalho, José Maria; Nalon, Gustavo Henrique; Pedroti, Leonardo Gonçalves; Oliveira de Paula, Marcos (Frontiers in Built Environment, 2025)
The furniture hub of Ubá, one of the foremost furniture production centers in Brazil, generates substantial volumes of unmanaged wood waste. This study quantifies the generated waste and evaluates its potential for reuse in the production of composite wood panels for eco-efficient buildings. Data from 17 different companies were analyzed in terms of production demand, quantities and types of raw materials, procedures to prevent storage losses, consumption and types of wood waste, waste disposal methods, etc. The total raw material consumption across all companies amounted to around 9,843,137 kg, with solid wood accounting for 662,375 kg (6.73%) and panels for 9,180,762 kg (93.27%). The total waste generated was 884,858 kg, including 458,058 kg (51.77%) of chips and 426,800 kg (48.23%) of sawdust, resulting in an overall waste generation of 9.0% by weight. These quantitative projections indicated sufficient availability of wood waste to sustain local manufacturing of composite panels, woodcrete, bio-based insulation materials, lightweight composites, and other sustainable solutions for civil construction. Eucalyptus and pine residues, predominant in the region, demonstrate high suitability for incorporation into recycled panels, enhancing resource efficiency. These findings highlight the strong potential for integrating wood waste recycling into the local construction industry, promoting environmental sustainability and circular economy practices in the region.